Inflammatory caspases: key regulators of inflammation and cell death - Fernández, Daniel Jiménez; Lamkanfi, Mohamed (Biological chemistry, 2015)
The innate immune system represents the first line of defence against infectious agents, and co-ordinates cellular and molecular mechanisms that result in effective inflammatory and anti-microbial responses against pathogens. Infection and cellular stress trigger assembly of canonical and noncanonical inflammasome complexes that activate the inflammatory caspases-1 and -11, respectively. These inflammatory caspases play key roles in innate immune responses by inducing pyroptosis to halt intracellular replication of pathogens, and by engaging the extracellular release of pro-inflammatory cytokines and danger signals. In addition, the inflammatory caspases-4, -5 and -11 were recently shown to directly bind microbial components. Although the immune roles of caspase-12 are debated, it was proposed to dampen inflammatory responses by interfering with caspase-1 activation and other innate immune pathways. Here, we recapitulate the reported roles of inflammatory caspases with an emphasis on recent insights into their biological functions.